Technical clearance for mental disorders among the servers in the city hall of Manaus: a preliminary analysis - Vívian Silva Lima Marangoni; André Luiz Machado das Neves; Zilmar Augusto de Souza Filho; Gizelly de Carvalho Martins (Semina: Ciências Biológicas e da Saúde, 2017)
This study aimed to investigate the occurrence of work absenteeism due to mental disorders among the servers of the Prefeitura Municipal de Manaus - PMM, registered by the Junta Médica do Município, in the period January to December 2011. It was found, after the documentary analysis, data of extreme significance that converge with numerous studies which indicate the nature of work as a risk factor for mental illness. It is through them that mental disorders has been a major cause of absence from work activities, especially among the servers in the area of health and education, representing 10% of total permits issued in 2011. These findings may support future studies that focus on health promotion and quality of life of these professionals, thus becoming a major challenge for policy makers